2014
DOI: 10.2337/db14-0500
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Corticotropin-Releasing Hormone–Induced Insulinotropic Role by High-Altitude Hypoxia

Abstract: We have shown that hypoxia reduces plasma insulin, which correlates with corticotropin-releasing hormone (CRH) receptor 1 (CRHR1) in rats, but the mechanism remains unclear. Here, we report that hypobaric hypoxia at an altitude of 5,000 m for 8 h enhances rat plasma CRH, corticosterone, and glucose levels, whereas the plasma insulin and pancreatic ATP/ADP ratio is reduced. In islets cultured under normoxia, CRH stimulated insulin release in a glucose-and CRH-level-dependent manner by activating CRHR1 and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…Glucose metabolism has been shown to differ at altitude; for instance, an association between polycythaemia and glucose intolerance has previously been described in an Andean population [12]. A study in rats showed that exposure to hypobaric hypoxia is associated with reduced insulin release due to inhibition of corticotrophin-releasing hormone [19]. This has also been replicated in clinical research; a recent publication by our group found that a 5% decrease in oxyhaemoglobin saturation was strongly associated with a HbA 1c value ≥ 48 mmol/mol (≥ 6.5%) (Miele C et al personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose metabolism has been shown to differ at altitude; for instance, an association between polycythaemia and glucose intolerance has previously been described in an Andean population [12]. A study in rats showed that exposure to hypobaric hypoxia is associated with reduced insulin release due to inhibition of corticotrophin-releasing hormone [19]. This has also been replicated in clinical research; a recent publication by our group found that a 5% decrease in oxyhaemoglobin saturation was strongly associated with a HbA 1c value ≥ 48 mmol/mol (≥ 6.5%) (Miele C et al personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Rats in the hypoxia group were placed in a hypobaric chamber (Avic Guizhou Fenglei Aviation Armament Co., Ltd, China, FLYDWC-50-IIC) and exposed to hypobaric hypoxia of 7000 m altitude (41.02 kPa, 8.2 % O 2 ) for 1, 4 or 8 h with or without CP154,526 (CRHR1 antagonist, 30 mg/kg, intraperitoneal (ip)) or 5000 m altitude (54.02 kPa, 10.8 % O 2 ) for 2 days [ 19 ]. The normoxia group was placed in the same chamber set at sea level (100.08 kPa, 20.9 % O 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…[37] Mice at p9, p14, p28, and p35 were deeply anesthetized with ether and decapitated and the hippocampi were removed, immediately frozen in liquid nitrogen, and stored at −80 °C. Control newborn mice were set at sea level (21.0% O 2 ) in a similar chamber.…”
mentioning
confidence: 99%